Relevance of various cavity aspect ratios to the thermal behavior of natural convection heat transfer for water-based hybrid nanofluid within a U-shaped enclosure - Asmadi, M. Solleh; Md. Kasmani, Ruhaila; Siri, Zailan; Saleh, Habibis; Mt Aznam, Suazlan (2023)
The investigation of the effect of the U-shaped cavity aspect ratio on the natural convection heat transfer of copper-alumina/pure water hybrid nanofluid is presented in the manuscript. Various aspect ratio of the enclosure is examined with fixed parameters to observe their effect on the overall thermal performance within the cavity. The dimensionless governing equations are formed, together with the thermophysical properties of hybrid nanofluid which are coupled and solved using the Galerkin weighted residuals finite element method bounded by the boundary conditions. A damped Newton-Raphson algorithm is employed as the convergence criterion to the hon-linear governing equations. Numerical and experimental comparisons between the present numerical results and previously published findings are conducted to ensure the solution's validity. An independent mesh test is done to ascertain the solution's independence from the meshing formation. The results are presented in the form of graphs, streamlines, and isotherms to see the effect of various parameters such as nanoparticle volume fraction and its ratios, Rayleigh number, and enclosure aspect ratios, and the discussion on the results is extensively presented. The present investigation is novel in terms of one heating wall instead of three heating walls in the previously published papers. It is hoped the findings in this manuscript will benefit heat transfer management in industries such as laptop and smartphone manufacturing.